Complete training evaluation the comprehensive guide to measuring return on investment - Griffin, Richard 1963- (Kogan Page, 2014)
While substantial advances have been made in the L&D profession over the last decade, evaluation remains by far the weakest part of the L&D cycle. Most organizations wish to evaluate the impact of their investment in training, but few do it well and the lack of effective methods is one of the key barriers.Complete Training Evaluation addresses these issues by providing practitioner friendly but academically robust information and guidance on how to evaluate all forms of learning and development. It draws on the author's own multidisciplinary research along with his practical experience of working with private and public sector organizations carrying out evaluation. The book provides practitioners with accessible "how-to" knowledge and tools to undertake evaluations of both formal and informal learning.Full of case studies and practical examples of application of methods and insights, Complete Training Evaluation equips practitioners with a range of approaches that can be used depending on the training program, capacity and capability--Publisher.